INCOME TAX BEFORE AND AFTER IMPLEMENTATION OF GOVERNMENT REGULATION NO.46/2013’S - Elmi Rakhma Aalin; Wiwik Kusumaning Asmoro; Bima Rachmadiawan (Riset Akuntansi Keuangan, 2018)
The purpose of this research is to analyze income tax before and after implementation of government regulation number 46 in 2013. This research is quantitative descriptive and use secondary data. Implementation of  government regulation number 46 in 2013 give direct impact for increasing income tax. Income tax increase also influencing by some factors, such as tax payer’s compliance, performance of tax officer, government policy, and economic condition in Indonesia.